2019
DOI: 10.1016/j.heliyon.2019.e01577
|View full text |Cite|
|
Sign up to set email alerts
|

Titanium-based nanocomposite materials for arsenic removal from water: A review

Abstract: Arsenic is highly carcinogenic element and less concentration of this chemical element makes natural water unsafe for human consumption. Versatile techniques including adsorption method have been established to remove the arsenic from water. However, adsorption is found to be one of effective method for the remediation of arsenic from contaminated water. Different types of natural adsorbents i.e. clays, waste materials, carbon based material have been studied widely for the adsorption of arsenic. Recently, nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 92 publications
(113 reference statements)
0
28
0
Order By: Relevance
“…These correspond to (1) a concentration were no toxic effects were seen; and (2) a concentration where the substance-induced observable toxic effects. Mixture solutions were prepared in complete culture media and left in an orbital shaker for 24 h, at room temperature, to allow for adsorption equilibrium of metals to NPs [39,40]. Triton X-100 1% (24 h exposure) was used as the positive control in both assays.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…These correspond to (1) a concentration were no toxic effects were seen; and (2) a concentration where the substance-induced observable toxic effects. Mixture solutions were prepared in complete culture media and left in an orbital shaker for 24 h, at room temperature, to allow for adsorption equilibrium of metals to NPs [39,40]. Triton X-100 1% (24 h exposure) was used as the positive control in both assays.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…In addition to natural sources such as weathering of As-rich minerals, arsenic penetrates into water by the burning of fossil fuels, use of As-containing pesticides, herbicides, poorly managed discharge from metallurgical and mining industries [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the use of salicylic acid-based NPs enhances As remediation by Isatis cappadocica [125] while the use of nano-Zn improved As stabilization by Helianthus annuus [126]. A review summarized that the composites of nano titanium (Ti) such as Zr-TiO2 and TiO2-αFe2O3Ce-Ti oxide are frequently used to treat As-contaminated water [127]. The application of TiO2, Si NPs and Au NPs has been found to counteract the toxic effects of different metals in Zea mays [128], Glycine max Application of nanoparticles for the management of contaminated agricultural lands and improvement of plant growth and developments has shown significant prospects [26].…”
Section: Nanotechnological Approaches To Enhance Phytoremediationmentioning
confidence: 99%